Growth Performance and Carcass of Two Different Strain of Broiler Subjected to Different Feed Restriction Methods - Mulyantini, Ni Gusti Ayu; Lole, Ulrikus Romsen (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The aims of study were to analyze if there is a difference in growth performance of two different strain fed commercial diet with either ad libitum or restricted methods. Two hundred sixteen (216) broiler chicks were allocated to 6 treatments with 6 replicates of 6 chicks/replicate. The experiment used a factorial design 2x3 with 2 strains, and 3 feeding methods, as follows: 1) ad libitum defined in Cobb 500 guidelines as control, 2) quantity restriction (45% of the daily ad libitum consumption), 3) time restriction (standard feed offered for 10h/d). Chicks were exposed to feed restriction from 8-14d. Then, the chickens were fed ad libitum until 35 days of age. The results show that feed restriction significantly (P<0.05) improved feed conversion ratio (FCR) and reduced abdominal fat. Growth performance of broiler fed ad libitum and quantity restriction were significantly (P<0.05) higher than those of time restriction feeding. The growth performance and carcass of strain A were not significantly (P>0.05) different from that of strain B. In conclusion, ad libitum and quantity restriction provide greater growth performance and carcass, but implementing time feed restriction could be a useful for improving FCR and reducing abdominal fat in broiler strains